Estrategias de fortalecimiento del clima laboral en los docentes de secundaria en la Unidad Educativa “Juan Abel Echeverría” de la cuidad de Latacunga. - Anahí Patricia, Molina Ramos (2023)
The current work was carried out as aim to propose strategies for strengthening the work environment in the "Juan Abel Echeverria" Educational Unit. The main problem to solve, it was the inadequate work environment in the educational institution, manifested by reduced work performance and low motivation in teachers, due to unattractive salaries and the viable strategies identification decline for improving the work environment. For addressing this problem, it was used a quantitative approach work methodology, what consists the data collection and interpretation. It was collected the information, through numerical and statistical interpretations, using research instruments, such as the questionnaire to measure the scientific authors group work environment PGR strategic plan for the 2015 year from Brazil, which has 5 dimensions, what are: 1. Autonomy, 2. Cohesion, 3. Support, 4. Recognition and 5. Innovation. The questionnaire was answered by the teachers and administrators from institution and it was made a documentary bibliographical research to theoretically support the study. The most relevant results regarding the work environment within the institution were found not adequate. The project practical application consisted in the competitive strategies plan creation for strengthening the work environment in the educational unit.